2010
DOI: 10.1074/jbc.m109.088708
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin Promotes Macrophage Polarization toward an Anti-inflammatory Phenotype

Abstract: It is established that the adipocyte-derived cytokine adiponectin protects against cardiovascular and metabolic diseases, but the effect of this adipokine on macrophage polarization, an important mediator of disease progression, has never been assessed. We hypothesized that adiponectin modulates macrophage polarization from that resembling a classically activated M1 phenotype to that resembling alternatively-activated M2 cells. Peritoneal macrophages and the stromal vascular fraction (SVF) cells of adipose tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
431
2
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 550 publications
(453 citation statements)
references
References 43 publications
15
431
2
5
Order By: Relevance
“…We observed that adiponectin deficiency resulted in severe psoriasiform inflammation. Since it is widely known that inhibition of adiponectin upregulates TNF-a production from macrophages or adipocytes 25,43 , we expected that the increased skin inflammation in adiponectin-deficient mice was mainly due to the overexpression of TNF-a. Although TNF-a expression was indeed elevated in the inflamed skin of adiponectin-deficient mice, even more striking was the upregulated expression of Th17-related cytokines, IL-17A/IL-17F/IL-22.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed that adiponectin deficiency resulted in severe psoriasiform inflammation. Since it is widely known that inhibition of adiponectin upregulates TNF-a production from macrophages or adipocytes 25,43 , we expected that the increased skin inflammation in adiponectin-deficient mice was mainly due to the overexpression of TNF-a. Although TNF-a expression was indeed elevated in the inflamed skin of adiponectin-deficient mice, even more striking was the upregulated expression of Th17-related cytokines, IL-17A/IL-17F/IL-22.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, recent reports regarding adiponectin have been focusing on a new feature of adiponectin, an aspect as a regulator of immune responses 22,23 . A number of experimental studies suggest that adiponectin attenuates excessive inflammatory responses in a variety of tissues, especially in obesity-associated states [24][25][26] . Roles of adiponectin in the development of psoriasis, one of the obesitylinked diseases as mentioned above, have been also discussed in the vast past epidemiologic reports [27][28][29] .…”
mentioning
confidence: 99%
“…Adiponectin knockout mice display moderate insulin resistance in the liver and impaired glucose tolerance [32], and have activated macrophages in AT with increased secretion of proinflammatory cytokines such as MCP-1 compared with macrophages of wild-type mice [17,33]. Adiponectin knockout mice also appear to have more hepatic steatosis and activated Kupffer cells than wild-type mice [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, APN may be important in suppression of neuroinflammation by glial cells. Thus, APN might be critical in normalizing the imbalance between M1 and M2 microglial polarization states,30 while globular APN induces a proinflammatory response in human astrocytes 31. Thus, further investigation of the in vivo effects of APN on glia, including microglia and astrocytes, is warranted.…”
Section: Apn Actions In the Nervous Systemmentioning
confidence: 99%